Speradines B-D, oxygenated cyclopiazonic acid alkaloids from the sponge-derived fungus Aspergillus flavus MXH-X104. Issue 21 (27th May 2015) - Ma, Xinhua; Peng, Jixing; Wu, Guangwei; Zhu, Tianjiao; Li, Guoqiang; Gu, Qianqun; Li, Dehai
Abstract: Two new highly oxygenated hexacyclic cyclopiazonic acid (CPA) alkaloids, speradines B and C (1 and2 ), together with one new related tetracyclic oxindole alkaloid, speradine D (3 ), were isolated from the sponge derived fungus Aspergillus flavus MXH-X104. Among them, speradine C (2 ) possesses unprecedented 6/5/6/5/5/6 hexacyclic ring system and 4-oxo-1, 3-oxazinane ring. The structures including absolute configurations of1 –3 were deduced from the spectroscopic data, X-ray diffraction analysis and the computational method including the calculation of the chemical shifts and the electronic circular dichroism (ECD) spectra. Graphical abstract: